2008
DOI: 10.1002/ptr.2346
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of Morus alba leaves green tea extract on mice in chronic forced swimming model

Abstract: In this study, the effects of an aqueous extract of Morus alba leaves green tea (ME) on mouse behaviors (depression, anxiety, climbing activity and thermal response), muscle coordination and muscle strength were studied. Male IRC mice received a single intraperitoneal injection of either the ME, desipramine or diazepam. Thirty minutes after injection, the mice were tested in all experimental models. A significant antidepressant-like effect could be detected in the animals receiving either 100 or 200 mg/kg ME. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Preclinical studies suggest that green tea extract may possibly benefit patients with schizophrenia. For example, green tea extract: (1) enhances learning and memory in aged rats [Kaur et al 2008]; (2) causes antidepressant-like effects that are comparable to desipramine [Sattayasai et al 2008]; (3) ameliorates lipopolysaccharide (LPS)-induced sickness behavior [Singal et al 2006]; (4) induces anxiolytic effects [Vignes et al 2006]; and (5) reduces reserpine-induced oxidative hepatic damage [Al-Bloushi et al 2009]. As early as 2000 years ago, Chinese emperors made reference to the calming effects of green tea, but we are not aware of any clinical studies of EGCG's psychotropic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies suggest that green tea extract may possibly benefit patients with schizophrenia. For example, green tea extract: (1) enhances learning and memory in aged rats [Kaur et al 2008]; (2) causes antidepressant-like effects that are comparable to desipramine [Sattayasai et al 2008]; (3) ameliorates lipopolysaccharide (LPS)-induced sickness behavior [Singal et al 2006]; (4) induces anxiolytic effects [Vignes et al 2006]; and (5) reduces reserpine-induced oxidative hepatic damage [Al-Bloushi et al 2009]. As early as 2000 years ago, Chinese emperors made reference to the calming effects of green tea, but we are not aware of any clinical studies of EGCG's psychotropic properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, green tea extract: (1) enhances learning and memory in aged rats [Kaur et al . 2008]; (2) causes antidepressant-like effects that are comparable to desipramine [Sattayasai et al . 2008]; (3) ameliorates lipopolysaccharide (LPS)-induced sickness behavior [Singal et al .…”
Section: Introductionmentioning
confidence: 99%
“…A further research is needed to determine the regulatory effect of green tea on glucocorticoids receptors expression and the target genes involved in the reward learning process and the improvement of depressive symptoms. Furthermore, a significant antidepressant-like effect was detected in mice that received a single intraperitoneal injection of green tea in the forced swim test when compared with the control [28]. A cross-sectional study revealed that higher green tea and coffee consumption was associated with a lower prevalence of depressive symptoms, suggesting that higher consumption of green tea, coffee and caffeine may confer protection against depression [29].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Some studies have reported many different medicinal properties of mulberry leaves (Morus alba) like neuroprotective property, cardioprotective property, antidepressant property. [9][10][11] It is used as antiinflammatory, diuretic, expectorant and antidiabetic in traditional Chinese medicine. [12][13][14] So this study is undertaken to evaluate the hypoglycaemic effect of aqueous extract of leaves of Morus alba in Alloxan induced diabetic albino rats.…”
Section: Introductionmentioning
confidence: 99%